All About Chinese Culture - The Chinese Academy of History.
VIII, 338 p. 247 illus., 192 illus. in color.
Keywords: This book invites senior experts and scholars from the fields of Chinese archaeology and history to describe ten influential “national treasure-level” cultural antiquities. Spanning from the Neolithic Age to modernity and with content ranging from the origin of civilizations to the red cultural relics, the book covers cultural antiquities, including: the Clay Figurine, the Painted Pottery Plate with Coiling Long Pattern (from the Neolithic Period), the Turquoise-inlaid and Long-shaped Bronze Object (of the Xia Dynasty), the Ivory Goblet Inlaid with Turquoise (of the Shang Dynasty), the He Zun (Ritual Wine Vessel), the Ox-shaped Zun (Wine Vessel), the Arm Protector with Animal and Clouds (and embroidered with the Chinese characters meaning “five stars appear in the East, which is a sign of Chinese victory over the Qiang”), the Beast-head-shaped Agate Cup (of the Tang Dynasty), the Imperial Gilt Gold Mesh Crown with Two Upright Wings (of the Ming Dynasty), etc. The text features not only scientific rigor but is also enjoyable to read and thought-provoking.